PENGGUNAAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN STRATEGI (PICTURE AND PICTURE) UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA KELAS VII PADA MATERI TEKS PROSEDUR - Nora Yurianita (sarasvati, 2022)
This study aims to describe the improvement of procedural text writing in seventh grade students of SMP Negeri 4 Singingi, Singingi District, Kuantan Singingi Regency by using Problem Based Learning (PBL) Model with Picture and Picture Strategy. This research method is classroom action research. The research subjects were VII SMP Negeri 4 Singingi totaling 20 students. This research consists of two cycles. The data collection techniques used were observation, interviews, written test procedure text, and documentation. Data analysis used qualitative and quantitative descriptive analysis techniques. Validity of data with validity (democratic, process, dialogical) and triangulation. The results showed that the use of the Problem Based Learning (PBL) Model with the Picture and Picture Strategy could improve the ability to write procedural texts in terms of processes and outcomes in class VII students of SMP Negeri 4 Singingi. Improving the quality of the process can be seen from the role of teachers and students who have increased significantly in the implementation of learning. This is marked by the emergence of a positive response through the cooperative and enthusiastic attitude shown by students, as well as conducive learning conditions. Process improvements ultimately have a positive impact on increasing yields. The improvement in the results can be seen from the increase in the scores of students' written procedure text from cycle I to cycle II. The average score at the time of pre-action was 68.14, the average in the first cycle was 68.57, and the average in the second cycle was 80.64. The increase in the average score from pre-action to cycle II was 12.05.